The ratio of monocytes to lymphocytes in peripheral blood correlates with increased susceptibility to clinical malaria in Kenyan children. - Warimwe, G; Murungi, L; Kamuyu, G; Nyangweso, G; Wambua, J; Naranbhai, V; Fletcher, H; Hill, A; Bejon, P; Osier, F; Marsh, K (Public Library of Science, 2013)
BACKGROUND: Plasmodium falciparum malaria remains a major cause of illness and death in sub-Saharan Africa. Young children bear the brunt of the disease and though older children and adults suffer relatively fewer clinical attacks, they remain susceptible to asymptomatic P. falciparum infection. A better understanding of the host factors associated with immunity to clinical malaria and the ability to sustain asymptomatic P. falciparum infection will aid the development of improved strategies for disease prevention. METHODS AND FINDINGS: Here we investigate whether full differential blood counts can predict susceptibility to clinical malaria among Kenyan children sampled at five annual cross-sectional surveys. We find that the ratio of monocytes to lymphocytes, measured in peripheral blood at the time of survey, directly correlates with risk of clinical malaria during follow-up. This association is evident among children with asymptomatic P. falciparum infection at the time the cell counts are measured (Hazard ratio (HR)  =  2.7 (95% CI 1.42, 5.01, P  =  0.002) but not in those without detectable parasitaemia (HR  =  1.0 (95% CI 0.74, 1.42, P  =  0.9). CONCLUSIONS: We propose that the monocyte to lymphocyte ratio, which is easily derived from routine full differential blood counts, reflects an individual's capacity to mount an effective immune response to P. falciparum infection.